FUNCTIONS OF PERSONAL NAMES IN LATEST LATVIAN POETRY - Šuplinska, Ilga (Via Latgalica, 2008)
In the period of postmodern culture, a lot of importance is attributed to mythological thinking and to the decoding of myths and current cultural signs. Therefore, the use of „talking” personal names which are perceived symbolically becomes relevant. As semiotic research points out: „For the mythological conscience it is common to see the world as a book, where cognition equals reading, which is based on the mechanisms of decoding and identification”. (Lotmans, Uspenskis 1993: 35) That means that for a better comprehension of prose, also in postmodern texts one has to pay attention to the choice of personal names, their frequency, and the presence and characteristics of cultural connotations. Bearing in mind that features of postmodern texts are the disregard of genre borders and marginalism, it can hypothetically be assumed that similar attitudes towards the use of personal names can be found in poetry. However, considering both recent studies of personal names and of poetry, it is possible to conclude that poetry pays little attention to the studies of personal names. Personal names are not very common in poetic texts, and poets use them quite precautiously (unless they link it to the tendencies within postmodernism as mentioned above). The objective of this article is to describe the functionality of personal names in latest Latvian poetry. The methodological basis of the work was obtained by studying the works of semioticians (R. Jakobson, Y. Lotman, B. Uspenskiy, Y. Levin, etc,), using the practical experience of philological text analysis (O. Nikolina, J. Kazarin), as well as by studying the attitudes of particular authors towards personal names (V. Rudnev, P. Florensky, A. Losev, G. Frege). The sources for the research for this article were anthologies of four young poetesses who were born in the 1970s and made their debut at the turn of the century, from which anthroponyms where taken for description: Inga Gaile’s „Laiks bija iemīlējies” (Time was in love, 1999) and „Kūku Marija” (Pastry Maria, 2007), Andra Menfelde’s „tranšejas dievi rok” (Gods dig trenches, 2005), Liga Rundane’s „Leluos atlaidys” (Great absolution, 2004), and Agita Draguna’s „prāts” (Mind, 2004). When analyzing the expressions of personal name in these anthologies, and thereby looking for mutual interconnections both within one anthology and from a comparative angle, a cultural sight of the generation born in the 70s (or at least of the „reading” intellectual part of that generation) could be identified. It turns out that the frequency and the uniformity/diversity of the usage of personal names can reveal tendencies of a particular trend. Clear spatial and associative semantic borders are revealed in the poetry of Agita Draguna and Liga Rundane, although it should be mentioned that personal names are very rarely used in the poetry. In contrast, the poetry of Inga Gaile and Andra Manfelde features a diversity of personal names, a tendency of appellativization, and a variety of interpretations of personal names. In the poetry of L. Rundane and A. Draguna it is possible to distinguish groups of personal names which unequivocally reveal the existence of their worlds, and mark the values of the lyrics. In the poetry of these authors two groups of personal names can be distinguished: 1) Poets: Andryvs Yurdzhs, Rainis, Oskars Seiksts (in the poetry of L. Rundane), Anthony McCann, Fjodor Tjutchev, Omar Hayam, Arseny Tarkovsky (in the poetry of A. Draguna) 2) Mythical characters: Shiva, Isida, Zuhra, Djemshid (in the poetry of A. Draguna), Virgin Mary (Jumprova Marija, in the poetry of L. Rundane). In the poetry of L. Rundane, one’s world has a Latgalian identity. In contrast, in the poetry of A. Draguna the world is more sought for, whereas one’s values seem to come from Eastern concepts of the mind and the meaning of a human life. In the poetry of I. Gaile and A. Manfelde the use of a personal name is aimed at: - marking one’s space, but unlike in the poetry of the authors mentioned above, it is full of doubts and controversies not only on the emotional level, but also regarding the values that one is looking for. Therefore personal names serve to reveal these controversies, not just to acknowledge one’s space; - a self-extinguishment of personal names and their change into simulacra, - or the process of mythologization of everyday life. It can be concluded that the limited use of personal names, of separate names, and of phrases which start with a capital letter, such as the lack of persistence in changing pronouns and generic names into the status of personal names (Miracle, You, Father of Noise, etc), proves the intensity of the perception of the mythical world, an expression paradigm common for postmodernism. (L. Rundane, A. Draguna). The relatively free and manifold use of personal names, their changes into generic names (contextual appellativization), the quest for general notions (lexical meanings), and the desire to create them (Barbie, harlequin, Aivazovsky, Lennon, Tanya, etc.) on the one hand create sumulacra, and on the other hand emphasize a mythologization of everyday life and the possibilities of its use in literary texts (through the use of figures or palimpsests).